APPROACH TO BUILDING THE PROCESS OF EMPLOYMENT OF STUDENTS AND GRADUATES OF MEDICAL UNIVERSITIES - Marasulov, A.F.; Bazarbaev, Muratali (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article highlights the main components and problems of building the process of employment of students and graduates of medical universities. Deficiencies have been identified in the mechanism of employment and employment monitoring of graduates of medical universities. Ways to eliminate these issues and shortcomings have been identified based on the creation of “Employment System” a republican systematic online database of graduates of medical universities. The structural-functional scheme of the automated workplaces of interaction instances and units for the implementation of the employment process of students and graduates in the “Employment System” was compiled.